Associations of fasting plasma glucose and glycosylated hemoglobin levels at less than 24 weeks of gestation with hypertensive disorders of pregnancy: the BOSHI study - Seiya Izumi; Noriyuki Iwama; Hirotaka Hamada; Taku Obara; Mami Ishikuro; Michihiro Satoh; Takahisa Murakami; Masatoshi Saito; Takayoshi Ohkubo; Takashi Sugiyama; Shinichi Kuriyama; Nobuo Yaegashi; et al. (Endocrine Journal)
This study aimed to evaluate the associations of fasting plasma glucose (FPG) and glycosylated hemoglobin (HbA1c) levels at <24 weeks of gestation with hypertensive disorders of pregnancy (HDP) and compare the strengths of the associations of HDP with FPG and HbA1c levels. Totally, 1,178 participants were included in this prospective cohort study. HDP, FPG, HbA1c, and potential confounding factors were included in multiple logistic regression models. The number of HDP cases was 136 (11.5%). When FPG and HbA1c were included in the model separately, quartile 4 (Q4) of FPG (87–125 mg/dL) and HbA1c (5.2–6.3% [33–45 mmol/mol]) levels had higher odds of HDP than quartile 1. The odds ratios (ORs) were 1.334 (95% confidence interval [CI]: 1.002–1.775) for Q4 of FPG and 1.405 (95% CI: 1.051–1.878) for Q4 of HbA1c. When the participants were divided into two categories based on the cut-off value with the maximum Youden Index of FPG or HbA1c, the ORs for high FPG (≥84 mg/dL) or high HbA1c (≥5.2% [33 mmol/mol]) were 1.223 (95% CI: 1.000–1.496) and 1.392 (95% CI: 1.122–1.728), respectively. When both FPG and HbA1c were included in the model simultaneously, the statistical significance of Q4 of FPG disappeared, whereas that of HbA1c remained. In two-category models, the same results were obtained. High FPG and HbA1c levels at <24 weeks of gestation were risk factors for HDP in pregnant Japanese women. In addition, high HbA1c levels were more strongly associated with HDP than high FPG levels.